The Input Requirements of Conventional and Shariahcompliant Banking - Mariani Abdul Majid (The International Journal of Banking and Finance, 2010)
Islamic banking activities are limited within the scope of shariâ€™ah which is within the scope of socially responsible and ethical banking activities, different from that based on interest-based banking. This paper attempts to measure the input data required by shariâ€™ah-compliant banking in comparison with conventional banking to estimate their relative efficiencies and economies of and returns to scale. Cost and output distance functions were estimated for a sample of banks in 10 countries which operate both types of banking. The results showed that shariâ€™ah-compliant banking has higher input requirements relative to interest based banking, but exhibit superior average efficiency only in Malaysia but inferior average efficiency in cross-country analysis. There is little evidence of differences in economies/returns to scale between shariâ€™ah and conventional banks.